Fixed point theorems for a semigroup of generalized asymptotically nonexpansive mappings in CAT(0) spaces - Phuengrattana,W. (Springer Publishing Company, 2015)
In this paper, we prove the existence of common fixed points for a generalized asymptotically nonexpansive semigroup {Ts : s ∈ S} in CAT(0) spaces, when S is a left reversible semitopological semigroup. We also prove Δ- and strong convergence of such a semigroup when S is a right reversible semitopological semigroup. Our results improve and extend the corresponding results existing in the literature. © 2012 Phuengrattana and Suantai; licensee Springer.